O processo de filiação de crianças maiores aos pais adotivos - Albuquerque, Carolina Mendonça Muniz de (2016)
This study was based on the attendance, by this reasearcher as a judiciary analist, in four adoptions cases of children between four and ten years old, prosecuted at the Recife s Secound Childhood and Adolescece Court, along the year of 2013. On these cases, we verified the adoptee s difficulty to filiate with the adoptive mothers, wich caused great suffering, while they affectively approached the adoptive fatherss without any apparent setbacks. For that reason, to contribute to the development of the work whith older than four year old children s adoption (here refered as older child adoption ), preparing the adoptees and assisting the adoptive parents on the filiation process, we sought to identify these filiations particularities. Furthermore, we analyzed how the maternity and paternity was experienced on the adaptation period and, more, and the relation of the couple regarding the will to adopt related to the child s interaction with the adoptive figures. Thereunto, we conducted a psychoanalytic approach s reaseach, analysing adaptation periods attendance reports. As results, regarding the adoptive children, we verified that the precariousness on experiencing the parental imago s mourning affects the emotional reinvestment upon the new maternal figures. As for the adoptive families, we noticed that the difficulties experiencing the biological child s mourning interferes on the adoptive filiation. Especially, for the adoptive mothers, it required mourn being a mother as being the son s primary love object, since, because of the child s development, he will demand a different relationship pattern than the one experienced with a baby. Upon the findings, we hope to contribute to the development of new knowledge to base te adoptive families preparation, essential to the adoptions success.